Strategic Planning for IS/IT of XYZ Internet Service Provider Using Ward and Peppard Method - Febriyanti, Kadek Dwi; Samopa, Febriliyan; Ambarwati, Rita (IPTEK Journal of Proceedings Series, 2019)
PT. XYZ is one of the leading Internet service providers in East Java, Bali and Lombok. As an IT company that has the motto "The Quality Internet Service Provider", of course the role of IT is a significant thing, because with the IT all processes that are initially manual can turn out to be well automated. However, in practice the demand for the development of IS / IT systems from various divisions tends to be only concerned with the interests of the division itself. So that in the end the system produced by the IT Apps division to help a division is not in line with the interests of other divisions. This happens because the IT division does not have a long-term work program plan for developing systems that are adapted to the PT. XYZ business goals and become a top priority in the development of the IS / IT system. In the preparation of the IS / IT strategi c planning framework using the Ward and Peppard Model approach and in evaluating the elaboration of information systems strategic planning and business strategies using Balanced Scorecard and Critical Success Factors. Several analytical methods such as Value Chain Analysis, SWOT Analysis, PEST Analysis and Five Force Model Analysis are used to analyze internal and external business environments. Strategic Grid McFarlan Analysis is used to map application portfolios The result of this research is a blueprint of strategic plan IS/IT in PT. XYZ. Wich included recommendation for improvements in the network structure. While at the SI system is recommended for development id advanced ERP which affect the portofolio application to support the achievement of the vision and mission of the company.